Results of pediatric living donor compared to deceased donor liver transplantation in the PELD/MELD era: Experience from two centers on two different continents. (10th February 2016) - Yankol, Yucel; Fernandez, Luis A.; Kanmaz, Turan; Leverson, Glen E.; Mezrich, Joshua D.; Foley, David; Mecit, Nesimi; D'Alessandro, Anthony M.; Acarli, Koray; Kalayoglu, Munci
Abstract: The LDLT option in the pediatric population allows recipients to be transplanted early. A total of 202 consecutive pediatric liver transplants from two different institutions—108 (LDLT) and 94 (DDLT)—were retrospectively compared. Overall, one‐ and three‐yr patient and graft survival were similar between DDLT and LDLT. ACR was greater in recipients of DDLT at one and three yr (50.8% and 61.0%) compared to LDLT (30.8% and 32.2%) (p = 0.002). When the data were stratified according to PELD/MELD score, LDLT with a low score had better one‐ and three‐yr graft survival (96.2% and 96.2%) compared to DDLT (88.2% and 85.2%) (p = 0.02), with comparable patient survival (p = 0.75). Patient and graft survival were similar between DDLT and LDLT in the high PELD/MELD group. Lower incidence of ACR in both low and high PELD/MELD groups was (29.6% and 34.3%) for LDLT compared to DDLT (50.3% and 53.3%, p = 0.002 and p = 0.028, respectively). Regardless of PELD/MELD score, status, age group, and recipient weight, LDLT provides excellent patient and graft survival with a lower incidence of rejection compared to DDLT.